2009
DOI: 10.1095/biolreprod.109.078808
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Deficiency Blocks the Initiation of Meiosis of Germ Cells in the Developing Rat Ovary In Vivo1

Abstract: Vitamin A (retinol) is required for male and female reproduction as well as to support many developmental processes. In the male, meiotic entry of germ cells occurs after birth and throughout adulthood, whereas in the female, the entry into meiosis I occurs during embryonic development. Evidence from cultured embryonic ovaries suggests that the vitamin A metabolite, all-trans retinoic acid (atRA), initiates this process. However, in vivo evidence to support a normal role for atRA in meiotic entry is lacking. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 40 publications
0
48
1
Order By: Relevance
“…However, the conclusion that it is rete cells that affect both meiosis and follicle formation does not exclude the possibility that cells of the 'cell streams' may influence these events as these are also concentrated in areas rich in ovarian rete. A number of studies have identified retinoic acid as a key factor in controlling the initiation of meiosis (Koubova et al 2006, Li & Clagett-Dame 2009. In an elegant study, Bowles et al (2006) provides strong evidence indicating that in mouse translocation of mesonephric-derived retinoic acid to the ovary drives the initiation of meiosis.…”
Section: Meiosis Apoptosis and Follicle Formationmentioning
confidence: 99%
“…However, the conclusion that it is rete cells that affect both meiosis and follicle formation does not exclude the possibility that cells of the 'cell streams' may influence these events as these are also concentrated in areas rich in ovarian rete. A number of studies have identified retinoic acid as a key factor in controlling the initiation of meiosis (Koubova et al 2006, Li & Clagett-Dame 2009. In an elegant study, Bowles et al (2006) provides strong evidence indicating that in mouse translocation of mesonephric-derived retinoic acid to the ovary drives the initiation of meiosis.…”
Section: Meiosis Apoptosis and Follicle Formationmentioning
confidence: 99%
“…While experiments involving the Cyp26b knockout mouse model confirmed that XY germ cells are capable of responding to RA (just like XX germ cells) in this artificial situation, more direct evidence for RA's instructive role during natural XX germ cell meiosis came from analysis of VAD ovarian development. In rat embryos severely deficient for vitamin A (mothers fed just 1.5mg all-trans RA per gram of diet) the majority of XX germ cells remained undifferentiated and did not express Stra8 or enter meiosis (Li and Clagett-Dame 2009). This effect was dose-dependent: numbers of meiotic germ cells were decreased in moderately VAD embryos (fed 12mg all-trans RA per gram of diet) compared to controls (30% compared to 75%), and so too was the level of Stra8 expression in these ovaries (Li and Clagett-Dame 2009).…”
Section: Is Retinoic Acid Necessary For Meiosis?mentioning
confidence: 99%
“…In rat embryos severely deficient for vitamin A (mothers fed just 1.5mg all-trans RA per gram of diet) the majority of XX germ cells remained undifferentiated and did not express Stra8 or enter meiosis (Li and Clagett-Dame 2009). This effect was dose-dependent: numbers of meiotic germ cells were decreased in moderately VAD embryos (fed 12mg all-trans RA per gram of diet) compared to controls (30% compared to 75%), and so too was the level of Stra8 expression in these ovaries (Li and Clagett-Dame 2009). In that study, germ cell numbers remained unchanged between VAD and control ovaries, demonstrating that dietary intake of Vitamin A positively correlates with meiosis entry in XX fetal germ cells in rodents.…”
Section: Is Retinoic Acid Necessary For Meiosis?mentioning
confidence: 99%
“…Initiation of meiosis in the fetal ovary has been suggested to require retinoic acid (Bowles, Knight et al 2006). Germ cells fail to enter meiosis and remain undifferentiated in embryonic vitamin A-deficient ovaries, suggesting that retinol regulates the initiation of meiosis I (Li and Clagett-Dame 2009). Another study revealed, that RA-degrading enzyme Cyp26b1 in fetal testis is responsible to delay meiosis until postnatal development (Koubova, Menke et al 2006).…”
Section: Testis Development Spermatogenesis Female Fertilitymentioning
confidence: 99%